ON THE IMPACT OF THE AIRCRAFT’S AERODYNAMIC CHARACTERISTICS ON THE FLIGHT OPERATIONS SAFETY AND EFFICIENCY - Bondik , Oleksandr; Zarubinska, Iryna; Kosohov, Oleksandr (Science-based technologies, 2025)
The aircraft’s aerodynamic characteristics play a crucial role in determining of the Airline’s flight operations safety and efficiently. The impact of the aircraft’s aerodynamic characteristics onto the flight operations efficiency can result in higher fuel consumption, reduced range, reduced endurance, and higher operational costs. Regarding this, aircraft manufacturers need to continually improve aircraft’s characteristics to increase future Airline’s flight operations efficiency. This work focuses on the impact of the aircraft’s aerodynamic characteristics onto the overall effectiveness of flight operations and how can this impact be avoided. The purpose of this article is to present a new assessment approach of the impact of aircraft’s aerodynamic characteristics onto the flight operations efficiency. Methods: The article describes the runtime method which increase the Airlines flight operations efficiency regarding the aircraft’s aerodynamic characteristics. Results: An analytical model of the impact of aircraft’s aerodynamic characteristics onto the flight operations efficiency. Discussion: The proposed new approach will allow to increase the Airlines flight operations effectiveness regarding the aircraft’s aerodynamic characteristics. Future research will explore new models that will increase flight operations safety and efficiency regarding the aircraft’s aerodynamic characteristics.